2013
DOI: 10.1186/1743-422x-10-243
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A/Hong Kong/156/1997(H5N1) virus NS1 gene mutations F103L and M106I both increase IFN antagonism, virulence and cytoplasmic localization but differ in binding to RIG-I and CPSF30

Abstract: BackgroundThe genetic basis for avian to mammalian host switching in influenza A virus is largely unknown. The human A/HK/156/1997 (H5N1) virus that transmitted from poultry possesses NS1 gene mutations F103L + M106I that are virulence determinants in the mouse model of pneumonia; however their individual roles have not been determined. The emergent A/Shanghai/patient1/2013(H7N9)-like viruses also possess these mutations which may contribute to their virulence and ability to switch species.MethodsNS1 mutant vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 79 publications
3
55
0
Order By: Relevance
“…RNA binding as well as RIG-I and the E3 ligase Riplet binding [41] inhibit signaling and IFN activation in mouse cells. In a recent report by Dankar et al (2013), NS1 residues 103L and 106I of the A/HK/156/1997 (H5N1) HPAI strain were found to increase NS1 localization to the cytoplasm of infected mouse cells, and also to mediate increased binding to RIG-I, which correlated with decreased IFN-β production in infected mouse cells [24]. Thus the increased distribution of NS1 to the cytoplasm observed for MA NS1 mutants may also contribute to inhibition of type I IFN production.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…RNA binding as well as RIG-I and the E3 ligase Riplet binding [41] inhibit signaling and IFN activation in mouse cells. In a recent report by Dankar et al (2013), NS1 residues 103L and 106I of the A/HK/156/1997 (H5N1) HPAI strain were found to increase NS1 localization to the cytoplasm of infected mouse cells, and also to mediate increased binding to RIG-I, which correlated with decreased IFN-β production in infected mouse cells [24]. Thus the increased distribution of NS1 to the cytoplasm observed for MA NS1 mutants may also contribute to inhibition of type I IFN production.…”
Section: Discussionmentioning
confidence: 91%
“…NS1 aa residues 103L and 106I have also been linked to cytoplasmic localization of the H5N1 highly pathogenic avian influenza (HPAI) isolate A/HK/156/1997 NS1 protein in mouse cells, when expressed on the PR8 viral backbone [24]. With respect to these findings, it is possible the NS1 protein contains an additional domain that influences nuclear export or cytoplasmic retention spanning from aa 98 to 106.…”
Section: Discussionmentioning
confidence: 99%
“…7). We did not investigate CPSF30 binding of the NS1 proteins from PR/8, HK/97, and BrevM/18, as previous studies showed that BrevM/18 NS1 binds to CPSF30, whereas the NS1 proteins of PR/8 and HK/97 cannot (27,49). These results established a direct and, most likely, causal link between the capacities of IAV NS1 proteins from seasonal strains to bind to CPSF30 and limit ISG15 expression in infected cells.…”
Section: A Facs-based Assay Reveals Distinct Isg Expression Patterns mentioning
confidence: 93%
“…NS1 proteins expressed by seasonal H1N1 and H3N2 strains efficiently interacted with CPSF30. In contrast, the mallard/Ger (H3N2) and Anhui/2013 (H7N9) NS1 proteins were poor interactors, and others had previously determined similar failures for the NS1 proteins of highly and lowly pathogenic avian H5 subtype viruses (49,54).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, viruses with mutations that facilitate efficient transmission and replication in humans could cause a pandemic. Many amino acid substitutions have been shown to contribute to the adaptation of avian H5N1 viruses to mammalian hosts (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). In particular, the PB2, PB1, and PA subunits of the polymerase complex play a role in virus pathogenicity and efficient viral growth in mammals.…”
mentioning
confidence: 99%